Assessment of the Effects of Boron Nitride Nanoplatelets Reinforcement on the Physical and Mechanical Properties of the Geopolymer Prepared by Natural Kaolinite: An In Vitro Study - Hasanen Ali Alnamel; Hikmat J Abdul Baqi (Wolters Kluwer Medknow Publications, 2024)
Introduction: We aimed to assess the effects of the addition of boron nitride nanoplatelets on the physical and mechanical properties of the geopolymer prepared by natural kaolinite. Methods: The compressive strength and diametral tensile strength tests were conducted according to BS 1881-116:1983 and ASTM E9-89a(2000) using an atomic force max instrument. The surface microhardness of the geopolymer was evaluated using a Digital Vickers microhardness tester, following the guidelines outlined in ASTM E92-82(2003). The contact angle (wettability) tests were carried out according to ASTM D7334-08(2022). Results: There were statistically significant differences among all study groups regarding compressive strength, diametral tensile strength, surface hardness, and wettability (p < 0.001). Conclusion: The boron nitride nanoplatelets reinforcement has a significant impact on the compressive strength, diametral tensile strength, surface microhardness, and wettability of the geopolymer, providing valuable insights for future research and development in this field.